2021
DOI: 10.1002/pmrj.12579
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static stability in para‐athletes with cerebral palsy considering their impairment profile

Abstract: Background: Balance impairment is a common feature in people with cerebral palsy (CP), affecting the performance of daily-life and physical activities. Objectives: To (1) explore the absolute and relative intrasession reliability of two balance tests to assess dynamic and static balance in ambulant paraathletes with CP; (2) explore the relationships between the two balance tests to determine potential application in sport classification; (3) assess the differences between CP profiles (ie, spastic diplegia, ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…This is a very effi-cient model since scores of 1 or 2 in the root node (i.e., the observed impaired balance of the non-dominant or more affected leg in the side-step test) correctly classify 128.4 instances (93.1%) as moderate spastic hemiplegia. Recent research describes similar difficulties for maintaining balance stability, indicating differences in control postural strategies in para-footballers with CP during a one-leg stance position with the dominant [59] and when comparing both body sides [32]. Our findings are in line with Reina et al [14], who demonstrated that the mean velocity of the centre of pressures when performing a one-leg stance is the best predictor for discriminating between different levels of spastic hemiplegia.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This is a very effi-cient model since scores of 1 or 2 in the root node (i.e., the observed impaired balance of the non-dominant or more affected leg in the side-step test) correctly classify 128.4 instances (93.1%) as moderate spastic hemiplegia. Recent research describes similar difficulties for maintaining balance stability, indicating differences in control postural strategies in para-footballers with CP during a one-leg stance position with the dominant [59] and when comparing both body sides [32]. Our findings are in line with Reina et al [14], who demonstrated that the mean velocity of the centre of pressures when performing a one-leg stance is the best predictor for discriminating between different levels of spastic hemiplegia.…”
Section: Discussionsupporting
confidence: 88%
“…Para-footballers with eligible impairments of ataxia/athetosis exhibit a higher coefficient of variance when performing agility, sprint, and acceleration/deceleration skills, with and without ball dribbling, when compared to the other two CP football profiles of spasticity [18]. Moreover, recent research with this population evidence that this subgroup has greater limitations for both static and dynamic balance, and this fact would influence the performance of basic and specific motor skills differently [32]. Therefore, it is plausible to think that this variability affects the efficiency of the model for this CP subgroup, but also the overall model.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations